Logica delle deviazioni. Dal pensiero magico alla scienza empirica (Itinera, 2023)
This essay aims to deal with early forms of skepticism, which naturalized the animal Kingdom by removing it from the moral sphere of religious spiritualism.In the 17th century, the gradual shift from magical thinking to science had important implications in the study of monsters.Starting from the concept of anomaly, we define a new science of life where monsters dwel. We deal with human phenomena, the tremendus, described and explained as deviations from the norm, errors. In the second half of the 17th century, the most important Academies began to devote themselves to the study of portentuos marvels and the debate on monsters became central in Natural Science: it was during this period that monsters were placed on anatomical tables in order to be dissected and classified. Fundamental in this regard were the studies of the surgeon John Hunter, in whose collection we can admire numerous specimens of so-called double monsters. In the 18th century, thanks to the numerous studies by Étienne Geoffroy Saint-Hilaire and his son Isidore, we arrive at the new vision of monstruosities, finally considered as sufficient in themselves, as autonomous abjects and therefore concrete, accessible and observable. Finally, I will discuss the special relationship between science and spectacle, public an private. The monster embodies a very strong aesthetic end attractive power: the image is the most suitable medium for describing it.
Keywords: Anomaly, Tremendus, double monsters, portentuos, error.